2010
DOI: 10.1212/wnl.0b013e3181f39adc
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative basis of age-related cognitive decline

Abstract: Objective: To assess the contribution of dementia-related neuropathologic lesions to age-related and disease-related change in cognitive function. Methods:A total of 354 Catholic nuns, priests, and brothers had annual clinical evaluations for up to 13 years, died, and underwent brain autopsy. The clinical evaluations included detailed testing of cognitive function from which previously established composite measures of global cognition and specific cognitive functions were derived. As part of a uniform neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
169
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(178 citation statements)
references
References 29 publications
7
169
1
1
Order By: Relevance
“…Age-related declines in general cognition have been well recognized (HĂ€llgren, Larsby, Lyxell, & Arlinger, 2001;Humes, 2005;Van Rooij & Plomp, 1990;Wilson, Leurgans, Boyle, Schneider, & Bennett, 2010). One cognitive function that is particularly relevant to success in speech recognition for individuals with hearing loss, and has been used to document evidence of age-related declines, is verbal working memory (WM; e.g., Bopp & Verhaeghen, 2005;Kumar & Priyadarshi, 2014;Nittrouer, Lowenstein, Wucinich, & Moberly, 2016;Rönnberg et al, 2013).…”
Section: Defining Working Memorymentioning
confidence: 99%
“…Age-related declines in general cognition have been well recognized (HĂ€llgren, Larsby, Lyxell, & Arlinger, 2001;Humes, 2005;Van Rooij & Plomp, 1990;Wilson, Leurgans, Boyle, Schneider, & Bennett, 2010). One cognitive function that is particularly relevant to success in speech recognition for individuals with hearing loss, and has been used to document evidence of age-related declines, is verbal working memory (WM; e.g., Bopp & Verhaeghen, 2005;Kumar & Priyadarshi, 2014;Nittrouer, Lowenstein, Wucinich, & Moberly, 2016;Rönnberg et al, 2013).…”
Section: Defining Working Memorymentioning
confidence: 99%
“…22 We reported previously that APOE e4 was associated with both preterminal and terminal decline. 23 Therefore, we explored the influence of the 9523 variant on terminal decline by using random change point models, a common modeling approach for nonlinear change.…”
mentioning
confidence: 91%
“…While previous studies have confirmed the existence of terminal decline, [3][4][5][6][7] they have inadequately addressed practice or learning effects in cognitive test performance. Practice effects refer to the improvement in cognitive test scores over repeated administrations of cognitive tests.…”
mentioning
confidence: 98%
“…However, even in the absence of clinically diagnosed dementia, and after accounting for other illnesses, declining cognitive function is also associated with mortality. [1][2][3][4][5][6][7] Therefore, cognitive decline could reflect biological aging independently of dementia. The concept of terminal cognitive decline refers to the relatively precipitous drop in cognitive function occurring in the years preceding death.…”
mentioning
confidence: 99%
See 1 more Smart Citation